Judaism and imperial ideology in late antiquity - Sivertsev, Alexei, 1973- (Cambridge ; New York : Cambridge University Press, 2011)
"This book explores the influence of Roman imperialism on the development of Messianic themes in Judaism in the fifth through the eight centuries CE. It pays special attention to the ways in which Roman imperial ideology and imperial eschatology influenced Jewish representations of the Messiah and Messianic age. Topics addressed in the book include: representations of the Messianic kingdom of Israel as a successor to the Roman Empire, the theme of imperial renewal in Jewish eschatology and its Roman parallels, representations of the emperor in late antique literature and art and their influence on the representations of the Messiah, the mother of the Messiah in late antique and Byzantine cultural contexts, and the figure of the last Roman Emperor in Christian and Jewish tradition"--Provided by publisher.
Introduction -- 1. Esau, Jacob's brother -- 2. Coronation in the temple -- 3. Mother of the Messiah -- 4. Renovatio imperii -- 5. King Messiah -- Conclusion.
Includes bibliographical references (p. 223-244) and index.
Description based on print version record.
Keywords: Messiah -- Judaism; Messianic era (Judaism); Judaism -- History -- To 1500.; Jews -- Civilization -- Roman influences; HISTORY / Ancient / General; RELIGION / Judaism / Theology; Electronic books